Plant spacing and weed control affect sunflower stalk insects and the girdling behavior of Dectes texanus (Coleptera: Cerambycidae). - Michaud, J. P.; Stahlman, Phillip W.; Jyoti, J. L.; Grant, A. K. (My University, 2009)
We conducted a 2-yr study to determine the effects of crop density and weeds on levels of damage caused by stalk-boring insects in rain-fed sunflowers in west-central Kansas. Weed-free sunflower had higher seed weight and oil content in 2007, but not in 2006, but weeds did not affect infestation by stalk-boring insects in either year. High-density sunflower had lower estimated seed yield per unit area than low-density sunflower in both years, but percentage oil was slightly greater in the high-density treatment in 2006. Sunflowers were more heavily infested by larvae of Ataxia hubbardi Fisher, Cylindrocopturus adspersus (Leconte), and Pelochrista womanana (Kearfott) in 2006 than in 2007, ostensibly as a result of being planted earlier. Larvae of Dectes texanus LeConte appeared unaffected by planting date and were present in >70% of plants in both years. Conditions during the period of crop maturity were much drier in 2006 than in 2007 and were associated with higher seed oil content and earlier and faster progression of stalk girdling by D. texanus larvae in both low- and high-density plots. There was also a strong effect of plant density on girdling behavior that seemed to be mediated by effects on soil moisture. Stalk girdling began earlier in high-density plots and a larger proportion of plants were girdled compared with low-density plots on all sampling dates in both years. Certain cultural tactics, in particular reduced plant spacing, have potential to delay the onset of girdling behavior by D. texanus larvae and thus mitigate losses that otherwise result from the lodging of girdled plants.
Citation: Michaud, J., Stahlman, P., Jyoti, J., & Grant, A. (2009). Plant Spacing and Weed Control Affect Sunflower Stalk Insects and the Girdling Behavior of Dectes texanus (Coleoptera: Cerambycidae). Journal of Economic Entomology, 102(3), 1044-1053. https://doi.org/10.1603/029.102.0324
Keywords: Ataxia hubbardi; Cylindrocopturus adspersus; Lodging; Plant population; Soil moisture